Chirality of Fingerprints: Pattern- and Curvature-Induced Emerging Chiroptical Properties of Elastomeric Grating Meta-Skin - Ki-Jae, Jeong (American Chemical Society, 2022)
Fingerprint-inspired elastomeric grating meta-skin (EGMS) is herein fabricated to investigate the chirality of fingerprints. The EGMS is made by a facile nanoimprinting method with a diffraction grating as a template using polydimethylsiloxane, followed by gold deposition. The chirality of the surface is caused by symmetry breaking, induced by the pattern (P) and curvature (T). Furthermore, the chiroptical properties of EGMS are reconfigurable through the control of the skew angle (θ), which is the angle between P and T. The chiroptical properties of a fingerprint are also shown and interpreted in this perspective. On the basis of the results, we suggest the strategy to impart chirality on the surface, which is reconfigurable by controlling P and T. It will be a useful method to produce chirality in membranes, thin films, metasurfaces, and 2D nanomaterials, as well as advance biometric recognition.